Differential Evaluation of Multi-Index Components in Different Parts of Ophiopogon japonicus - Song, Jiuhua; Liu, Qin; Shi, Kai (Indian Journal of Pharmaceutical Education and Research)
Objectives: To establish a method for determination of 11 components content to evaluate their quality and compare the difference between tuberous root and fibrous root of Ophiopogon japonicus by multivariate statistical analysis. Materials and Methods: The contents of total saponins, total flavonoids and total polysaccharides were determined by ultraviolet-visible spectrophotometry. The mineral elements were determined by atomic absorption spectrophotometry. Cluster analysis, partial least squares discriminant analysis and principal component analysis model were used for discrimination and comprehensive quality evaluation of tuberous root and fibrous root. Results: The results showed that there were obvious differences among samples from different parts, the results of 3 kinds chemometrics method analysis were consistent, which indicates that multi-index component quantitative analysis combined with chemometrics can be used for plant part identification. The difference between the two type roots was obvious and the content of most components in tuberous root was significantly higher than that in fibrous root. Conclusion: The method is simple and efficient and can be used to distinguish tuberous root and fibrous root of Ophiopogon japonicus.
Keywords: Different parts; Differential evaluation; Ophiopogon japonicus.